SPEAKING ANXIETY OF ENGLISH DEPARTMENT STUDENTS AT UNIVERSITY OF DARMA AGUNG MEDAN - Corry Ester Margaret Siagian; Jenny Solita Duha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
The lecturer dominant proportion and students’ passivity in the classroom caused by many reason, students’ speaking anxiety is one of the main reason. Feeling ashamed to speak out their mind is a matter of the most of English learners’ problems from time to time. Finding out the factors contributes to students reluctantly talking in English is worth searching in order to create a successful English speaking learning in the future. This present study aimed at investigating the speaking anxiety reasons of english department students of University of Darma Agung. To do so, the researcher asked 30 students to be participated in this qualitative study. They were required to fill out questionnaire and to be participated in an interview. This study revealed that the anxiety experienced by the students are due to three main reasons: 1) being afraid of bad respond; 2) feeling nervous and not dare to talk and 3) feeling afraid of making mistake, which are followed by other minor reasons for each main reason. The most occurred minor reason is students’ lack of vocabularies.